Dakwah di Kalangan Buruh Tani ( Studi Fenomenologi Pada Masyarakat Petani di Kecamatan Sukadana Kabupaten Lampung Timur) - Widodo, Anton; Muhajir, Muhajir; Rahmad, Andi; Anantama, Agam (Fakultas Dakwah dan Ilmu Komunikasi, 2021)
ABSTRACTAfter careful research, this study concludes that various forms of recitation used as a medium for delivering da'wah messages among the farming community are interpreted by the da'i and the community solely because to maintain good relations with Allah (habluminallah), good relations between others. human (hablumninannas), protecting and preserving nature (habluninalalam). The self-concept of the preacher as a da'wah actor is formed because there is a meaning by himself to the environment, namely the farming community who still needs da'wah in the midst of their busy lives, besides the reality of the recitation is formed because there is a feeling of the da'i and the community as a Muslim about the need to understand Islamic teachings in a holistic manner. khafah. The use of recitation as a medium for delivering da'wah messages is the only one that is most effective in Sukadana District as well as interaction between preachers and the people of Sukadana District in order to realize good habluminnas among fellow Sukadana District people who work as farmers